Differentiable and analyticFunction spaces (Journal of Humanitarian and Applied Sciences, 2023)
In this paper we shall prove a theorem which is very important for the structure of complete analytic vector fields, and some lemmas.
Keywords: differentiable; analytic function; analytical mapping and the class of C∞differentiable functions